ZAKAT PRODUKTIF DI PERKANTORAN BUMN: Studi Kasus di PT. Arun Kota Lhokseumawe Nangroe Aceh Darussalam - Marpuah Marpuah (Universitas Islam Negeri Imam Bonjol Padang, 2014)
The development of zakat practices in Indonesian Islam at the last two decades has shown that this religiousobligation has gradually been transforming from as merely religious matter shifting to economic factor as well.This study examines the actual practices of zakat among zakat payers (muzakki) took places in a state company,that is PT.Arun Lhokseumawe, North Aceh. For this purpose, a field research was carried out to this companythat has estabalished a zakat institution. This study uncovers that the empolyers of this company decided thatMuslim employees should deduct 2,5 per cent for the monthly salary for the zakat. Further, the ʿāmil of zakatdistributed the collected revenue to the zakat recipients (mutaḥiq) which are for education, public facilities suchas mosques, living cost of the poor, health care, small-scale-business investment and adminisntrative expanses.In other words the collected revenue was not only distributed for the consumtive purposses, but was also forproductive matters. However, the distribution of the revenue was still mainly for the consumtive purposses.